2015
DOI: 10.1021/acsami.5b04884
|View full text |Cite
|
Sign up to set email alerts
|

Naphthodithiophene-Based Conjugated Polymer with Linear, Planar Backbone Conformation and Strong Intermolecular Packing for Efficient Organic Solar Cells

Abstract: Two donor-acceptor copolymers, PBDT and PNDT, containing 4,8-bis(2-ethylhexyloxy)benzo[1,2-b:3,4-b']dithiophene (BDT) and 4,9-bis(2-ethylhexyloxy)naphtho[1,2-b:5,6-b']dithiophene (NDT), respectively, as an electron-rich unit and 5,6-difluoro-2,1,3-benzothiadiazole (2FBT) as an electron-deficient unit, were synthesized and compared. The introduction of the NDT core into the conjugated backbone was found to effectively improve both light harvesting and the charge carrier mobility by enhancing chain planarity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Planar conjugated polymers such as ladder poly( p ‐phenylene)‐type polymers (LPPP) and graphite ribbon are special members of conjugated polymer family . The unique rigid and planar structure endows materials with good conjugation, carrier mobility, and luminescence intensity, so ladder conjugated polymers are widely applied as organic light emitting diodes and field‐effect transistor materials. LPPP polymer was first reported by Scherf and Müllen, graphite ribbon polymer was reported by Goldfinger and Swager .…”
Section: Homo and Lumo Energies And Band Gap Data Of Polymers P1 P2mentioning
confidence: 99%
“…Planar conjugated polymers such as ladder poly( p ‐phenylene)‐type polymers (LPPP) and graphite ribbon are special members of conjugated polymer family . The unique rigid and planar structure endows materials with good conjugation, carrier mobility, and luminescence intensity, so ladder conjugated polymers are widely applied as organic light emitting diodes and field‐effect transistor materials. LPPP polymer was first reported by Scherf and Müllen, graphite ribbon polymer was reported by Goldfinger and Swager .…”
Section: Homo and Lumo Energies And Band Gap Data Of Polymers P1 P2mentioning
confidence: 99%
“…[43] However, only very few NDT-based polymer donors have been reported due to the difficulty of synthesis, which are paired all with the traditional fullerene acceptors. [44][45][46][47] No work indicated that the NDT-based polymers have been used for matching the more superior NFAs at present.…”
Section: Introductionmentioning
confidence: 99%
“…The 2D patterns of the as‐cast, 200 °C, and 300 °C annealed films show both ( h 00) and (010) reflections along the out‐of‐plane direction, corresponding to lamellar and π–π stacking diffraction peaks, along both the out‐of‐plane and the in‐plane direction, respectively. These indicate that the crystalline textures of the polymer films are bimodal structures with coexisting edge‐on and face‐on crystallites . Two diffraction crystallographic peaks of β‐phase, α‐phase in the in‐plane direction are also observed from the polymer films with SFA side chains.…”
Section: Physical and Optical Properties Of Ptv‐btzfmentioning
confidence: 75%